PENGARUH PEMAKAIAN KONTRASEPSI IUD DENGAN KEJADIAN VAGINITIS DI PUSKESMAS GROGOL KABUPATEN SUKOHARJO - Arintowati, Yusnanda; Murtutik, Lilis; Suwarni, Anik (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
Background. The use of an IUD is one of the predisposing factors that can lead to vaginitis. On the use of IUDs found in the presence of vaginal discharge or vaginal body is due to the initial reaction to a foreign body. Objective: To determine the relationship with the IUD contraceptive use on the incidence of vaginitis Sukoharjo Sky View Health Center. Methods. using descriptive correlative techniques using cross- sectional design. The sampling technique used is to use sampling with a total sample size of 93. Data collection techniques with tools such as the master table. Test analysis in this study with statistical test t test. Results: Results of t test the effect of the IUD contraceptive use on the incidence of vaginitis Sky View Health Center Sukoharjo January to March 2013 obtained t - test results obtained -7.133 t . With the t table with df -4. 416 29. Mean results of the analysis indicate that the value of t count> t table and with a significance value of 0.001 calculated p < 0.05 p table. Conclusion : There is significant relationship between the incidence of IUD contraceptive use vaginitis in Sky View Health Center Sukoharjo January to March 2013. Keywords : Contraception IUD , the incidence of vaginitis